Peran Akhlak Dalam Pengajaran Menurut Al-Ghazali: Perspektif Filsafat Pengajaran - Azzura Arum Ningtias; Sari Primayeni; Herlini Puspika Sari (SURAU : Journal of Islamic Education, 2024)
This research aims to examine the role of morals in education according to Al-Ghazali from the perspective of Islamic educational philosophy, with a focus on its relevance in forming the character of students. This research uses a qualitative method with a library research approach. Data was collected through analysis of Al-Ghazali's main works, such as Ihya' Ulum al-Din and Mizan al-'Amal, as well as other supporting literature related to the concept of morals and Islamic education. Data analysis was carried out descriptively-analytically to reveal the concept of morals in education and its application in character development. The results of the research show that Al-Ghazali views morals as the core of education, which functions as a means to achieve human perfection (insan kamil). Education designed based on Al-Ghazali's philosophy emphasizes the integration of science, spirituality and the formation of noble character. This concept emphasizes that education must not only be oriented towards intellectual abilities, but also towards the formation of strong morals. Al-Ghazali's thoughts have significant relevance in the development of modern Islamic education, especially in efforts to build a generation of character, civility and high morals. AbstrakPenelitian ini bertujuan untuk mengkaji peran akhlak dalam pengajaran menurut Al-Ghazali dari perspektif filsafat pengajaran Islam, dengan fokus pada relevansinya dalam pembentukan karakter peserta didik. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi pustaka (library research). Data dikumpulkan melalui analisis terhadap karya-karya utama Al-Ghazali, seperti Ihya’ Ulum al-Din dan Mizan al-‘Amal, serta literatur pendukung lainnya yang berkaitan dengan konsep akhlak dan pengajaran Islam. Analisis data dilakukan secara deskriptif-analitis untuk mengungkap konsep akhlak dalam pengajaran serta penerapannya dalam pengembangan karakter. Hasil penelitian menunjukkan bahwa Al-Ghazali memandang akhlak sebagai inti dari pengajaran, yang berfungsi sebagai sarana untuk mencapai kesempurnaan manusia (insan kamil). Pengajaran yang dirancang berdasarkan filsafat Al-Ghazali menekankan pada integrasi antara ilmu pengetahuan, spiritualitas, dan pembentukan karakter mulia. Konsep ini menegaskan bahwa pengajaran harus tidak hanya berorientasi pada kemampuan intelektual, tetapi juga pada pembentukan akhlak yang kokoh. Pemikiran Al-Ghazali memiliki relevansi yang signifikan dalam pengembangan pengajaran Islam modern, khususnya dalam upaya membangun generasi yang berkarakter, beradab, dan bermoral tinggi.